Diseño de un modelo de administración para un hogar gerontológico - caso Hogar Gerontológico Mercy (2017)
This monograph consists of different parts, the first one refers to the general definitions of key words and the evolution of gerontology in human history. The second part is based on the description of gerontological homes, the clients of these, the most common diseases and the special treatment they should have. The third part refers to the laws which must be taken into account in Bogotá for these households. The fourth part focuses on the human resources of households, explaining the functions of each person in the work team. The fifth part, have a totally different approach until now had been working on gerontology, in this part and the approach is administrative, talking about the types of business.